The Relationship between Behavior in Using Online Media for Petanque Sports Recreation with Health Promoting Behaviors of the Elderly in Bangkok - Khamchan, Thirawut; Infahsaeng, Arpornranee; Sampatpong, Pornpimol (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
This research aimed to 1) study the online media usage behavior, 2) study the health promotion behavior, 3) compare the opinions on online media usage behavior classified by personal factors, 4) compare the opinions on health promotion behavior classified by personal factors, and 5) study the relationship between online media usage behavior for petanque recreation and health promotion behavior of the elderly in Bangkok. A questionnaire was used to collect data from 384 elderly people, aged 60 years and over who used online media for petanque recreation in Bangkok. The sampling method was purposive and convenience sampling. The statistics used for data analysis were frequency, percentage, mean, standard deviation, t-test, One-way ANOVA, and Pearson's product moment correlation coefficient. The results showed that 1) The behavior of using online media for petanque recreation of the elderly in general was at the highest level. When considering each aspect, it was found that all aspects were at the highest level. The aspect of openness to experience was the aspect with the highest average value. 2) The behavior of promoting health of the elderly in general was at the highest level. When considering each aspect, it was found that all aspects were at the highest level. The aspect of responsibility for health was the aspect with the highest average value. The results of the hypothesis testing found that 1) The elderly with different statuses and occupations had different opinions about online media usage behaviors in general and in each aspect at a statistical significance level of .05. 2) The elderly with different statuses and occupations had different opinions about health promotion behaviors in general and in each aspect at a statistical significance level of .05. 3) The relationship between online media usage behaviors and health promotion behaviors of the elderly in Bangkok had a high level of relationship in the same direction. The aspect of seeking information had a high level of relationship in the same direction with health promotion behaviors in general, ranked first, with a statistical significance level of .01.